SUBCOMMISSURAL IMPLANTATION OF AORTIC PROSTHESES WITH THE USE OF THE NONCORONARY SINUS AND THE FIBROUS TRIGONES - Liotta, Domingo (1979)
The technique described here permits insertion of a large prosthesis into a small aortic annulus and avoids the necessity of additional procedures for enlarging the aortic ring. Inspection of the fibrous skeleton of the heart reveals that the large intervalvular trigone and the noncoronary sinus of Valsalva are remarkably elastic. Full advantage of this natural elasticity is achieved by suturing the prosthesis to the base of these structures from outside the aorta. Sutures are placed in the sinuses of the right and left cusps in the usual manner. Judicious application of this procedure allows the implantation of a No. 23 or No. 24 prosthesis in cases that would require a No. 19 or No. 21 with the use of conventional methods.